PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH BERBASIS MEDIA AUDIO VISUAL SITUS PURBAKALA PUGUNG RAHARJO UNTUK MENINGKATKAN KESADARAN SEJARAH SISWA KELAS X SMA NEGERI 1 KOTAGAJAH - Aurora Nandia F , Herman J Waluyo, Samsi Haryanto (Jurnal Ilmiah Dikdaya, 2017)
The Product that expected in this research is a product of learning the history of media based on media audio visual The Site of Ancient Pugung Raharjo that packed in the form of learning video to raise awareness of the history of student learning and achievement. The purpose of this research are (1) to know the media teaching history which have so far carried out in SMA Negeri 1 Kotagajah, (2) to know the media teaching of history which have carried out in SMA Negeri 1 Kotagajah, (3) to know the process of development video media teaching of history based on visualize The Site of Ancient Pugung Raharjo, (4) to examine media effectiveness of teaching history by using audio and visual based The Site of Ancient Pugung Raharjo in order to raise awareness of history and student learning achievements.The method used in this research are using methods descriptive and evaluative. To compile the condition of being stay on the ground used method of descriptive. Meanwhile, to evaluate the audio-visual media feasibility study on the development used test method of evaluative. Dekriptif analysis results are obtained that the media used in the process of learning at SMA Negeri 1 Kotagajah by media text books and media in the form of microsoft office powerpoint.The attitude of the consciousness of history and learning achievements of students are still low as seen from pretest that given to students. The development of media audio visual based on the site of ancient pugung raharjo by validation through expert test material, media experts, one-on-one, trial test of small group, and field test with average revenue of any tests are more than 3.5 so that we can conclude that the media is in the category of good and worthy for used as an instrument of research. for test the effectiveness of history shows the awareness and learning achievements students who use media audio visual based on the site of ancient pugung raharjo are better than the students who use media powerpoint if it would be compared. Keywords : Media Audio Visual for Learning, Awareness of History, Learning Achievements